COMPARATIVE ANALYSES OF THE THERMAL PERFORMANCE OF REFRIGERANTS R134A, R245fa, R407C AND R600a DURING FLOW BOILING IN A MICROCHANNELS HEAT SINK - Leão, H. L. S. L.; Marchetto, D. B.; Ribatski, G. (Revista de Engenharia Térmica, 2018)
A comparative study of the performance of of refrigerants R134a, R407C, R245fa and R600a during flow boiling was performed for a 123x494 µm2 heat sink composed of 50 parallel rectangular microchannels. Heat transfer experimental results for heat fluxes up to 310 kW/m2, mass velocities from 300 to 800 kg/(m2 s), liquid subcoolings of 5 and 10 °C and saturation temperature close to 30 ºC were obtained. Global heat transfer coefficients (footprint) up to 10 kW/(m2 °C) were found. The liquid superheating necessary for the onset of nucleate boiling (ONB) was also characterized, and the fluids R245fa and R407C presented the highest and lowest, respectively, superheating to trigger the boiling process. Moreover, for a fixed averaged vapor quality, the average effective heat transfer coefficient increases with increasing mass velocity and liquid subcooling. The refrigerants R600a and R407C presented the highest and the lowest heat transfer coefficients, respectively. Five heat transfer predictive methods from literature provided accurate predictions of the data for R134a, R245fa and R600a, capturing most of the data trends. No one method provided accurate predictions of the heat transfer coefficient data of R407C.